Republic of Belarus : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Belarus continues to be highly vulnerable to economic shocks, as was illustrated by the turbulence in foreign exchange and debt markets in late 2014. Frequent bouts of expansionary macroeconomic policies, in a context of deep structural rigidities, have fueled inflation and external imbalances and left Belarus dependent on ad hoc external support. In 2015, growth has slowed sharply as high uncertainty, reductions in real incomes, administrative measures, and declining trade with Russia weighed on activity. The outlook is for a recession and continued external pressures. With Russia in a downturn, the Belarusian economy is projected to contract by 2.25 percent in 2015, led by falling exports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet